Strain-specific effects of Akkermansia muciniphila on the regulation of intestinal barrier - Yang Liu; Qing Liu; Chengcheng Zhang; Jianxin Zhao; Hao Zhang; Wei Chen; Qixiao Zhai (Food Science and Human Wellness)
Akkermansia muciniphila, one of the most promising next-generation probiotics, was reported to exhibit beneficial modulatory effects on the gut barrier. However, the strain-specific and underlying regulatory mechanisms of this species on gut barrier function were not well studied. Therefore, this study evaluated the protective effect of A. muciniphila strains on the intestinal barrier and investigated the mode of action and material basis of this modulatory effect. We first confirmed the strain-specific effects of A. muciniphila on intestinal barrier regulation and found that this phenomenon may be explained by the different abilities of strains to affect tight junction protein expression in enterocytes. Comparative genomic analysis proved that the ability of A. muciniphila to regulate the intestinal barrier was exerted in part by the functional genes (such as COG0438, COG0463, and COG2244) related to the synthesis of cellular surface proteins. The role of these surface proteins in intestinal barrier regulation was further verified by strain-comparative experiments in animal and cell models and surface protein removal trials. This study confirmed the different effects of A. muciniphila strains on gut barrier modulation and provided molecular and genetic targets for the screening of A. muciniphila strains with superior protection against gut barrier dysfunction.